MANAGEMENT OF EXPENDITURE RESPONSIBILITY LETTER AT THE BUREAU OF GOVERNMENT AND AUTONOMY OF THE EAST JAVA PROVINCE - Qomariah, Intan Ainur; Widodo, Djoko; Wahyono, Muchammad (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
The letter of responsibility (SPJ) is a report on the realization of expenditure from an activity that has been carried out. In Governance for the preparation of the SPJ at the Bureau of Government and Regional Autonomy, the implementation of activities and technical guidelines is based on the Peraturan Pemerintah Nomor 14 Tahun 2021. This study aims to identify and analyze the Stages of the Process for the Preparation of the Expenditure SPJ Management at the Regional Government and Autonomy Bureau of East Java Province. This study uses a type of qualitative descriptive method. Sources of data used in this study, namely primary data and secondary data obtained directly. The results of the study indicate that the East Java Provincial Government and Regional Autonomy Bureau is in the stage of managing the SPJ preparation, its management expenditure is in accordance with the Governor's Regulation which is the benchmark in its implementation, but there are several factors that hinder the current SPJ preparation process, such as lack of Human Resources, procrastination attitude. In addition, there is a lack of archives or documents. The advice given is to increase the number of non-permanent employees, especially in the Administrative Subdivision, to have deadlines in collecting reports and to add archive storage so that there are no obstacles in finding files.